Peran Lembaga Manajemen Kolektif Sebagai Bentuk Perlindungan Hukum Pencipta Lagu Dan Pemilik Hak Terkait - Elly Hernawati (Fakultas Hukum Universitas Surabaya, 2019)
Copyright is one of the Intellectual Property Rights components and should be paid attention to. Even more in technology era that developing, copyright protection needed to be enhanced, so that the right of creator, Copyright holder or owner of relevant rights can be protected and urge people to create. Indirectly, good and healthy business climate could be fostered. Not all people have skill to create, that is why those people who have skill to create must be protected and even awarded, hoping that people urged to create. One of the creations that protected are song and music. In creating song or music, creator involve recording producer, music director or arranger. Regarding the creation, creator holds moral and economy rights, while parties involved hold the relevant rights to it. Collective Management Agency is an agency that help creator or relevant rights owner in managing and distributing the creation which is song or music that being commercialized. Yet the creator must be the member of the agency beforehand. Commercialization of a song or music by user can rise problem. Protection to the song or music is for the whole thing, including lyric, notation, arrangement and song title. The utilization of a song or music should be still protecting the parties that hold the copyright and the relevant right to it.